Isolation and characterization of two homolog phages infecting Pseudomonas aeruginosa - Yuanyuan, Niu; Xiaobo, Yang; Shang, Wang; Yutong, Yang; Hongrui, Zhou; Chenyu, Li; Bin, Xue; Xi, Zhang; Chen, Zhao; Zhiqiang, Shen; Jingfeng, Wang; Yun, Ling; et al. (Frontiers in Microbiology, 2022)
Bacteriophages (phage) are capable of infecting specific bacteria, and therefore can be used as a biological control agent to control bacteria-induced animal, plant, and human diseases. In this study, two homolog phages (named PPAY and PPAT) that infect Pseudomonas aeruginosa PAO1 were isolated and characterized. The results of the phage plaque assay showed that PPAT plaques were transparent dots while the PPAY plaques were translucent dots with a halo. Transmission electron microscopy results showed that PPAT (65 nm) and PPAY (60 nm) strains are similar in size and have an icosahedral head and a short tail. Therefore, these belong to the short-tailed phage family Podoviridae. One-step growth curves revealed the latent period of 20 min and burst time of 30 min for PPAT and PPAY. The burst size of PPAT (953 PFUs/infected cell) was higher than that of PPAY (457 PFUs/infected cell). Also, the adsorption rate constant of PPAT (2.08×10-8 mL/min) was higher than that of PPAY (1.52×10-8 mL/min) at 5 min. Whole-genome sequencing of phages was carried out using the Illumina HiSeq platform. The genomes of PPAT and PPAY have 54888 and 50154 bp, respectively. Only 17 of the 352 predicted ORFs of PPAT could be matched to homologous genes of known function. Likewise, among the 351 predicted ORFs of PPAY, only 18 ORFs could be matched to genes of established functions. Homology and evolutionary analysis indicated that PPAT and PPAY are closely related to PA11. The presence of tail fiber proteins in PPAY but not in PPAT may have contributed to the halo effect of its plaque spots. In all, PPAT and PPAY, newly discovered P. aeruginosa phages, showed growth inhibitory effects on bacteria and can be used for research and clinical purposes.